2017
DOI: 10.1016/j.ekir.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Incremental 2-Times Weekly Hemodialysis in Incident Patients With Residual Kidney Function

Abstract: IntroductionWe hypothesized that at least half of incident hemodialysis (HD) patients on 3-times weekly dialysis could safely start on an incremental, 2-times weekly HD schedule if residual kidney function (RKF) had been considered.MethodsRKF is assessed in all our HD patients. This single-center, retrospective cohort study of incident adult HD patients, who survived ≥6 months on a 3-times weekly HD regimen and had a timed urine collection within 3 months of starting HD, assessed each patient’s theoretical abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 39 publications
0
40
0
1
Order By: Relevance
“…In this study, we used the deidentified urine collection database spanning 14 years that was used in a former study (consent not required due to retrospective deidentified data) approved by the University of California, Davis Institutional Review Board (protocol number 806282-1) and an administrative review of the dialysis provider (Dialysis Clinic, Inc) on evaluation of K RU in incident HD patients and theoretical twice-weekly HD. 7 For this study, K RU was determined by multiplying urine volume (Vol) in milliliters with the concentration of urine urea (U urea ) in milligrams per deciliter, divided by an adjusted plasma urea (P urea ) in milligrams per deciliter, which was the pre-HD plasma urea collected on the day that the urine collection terminated. The adjustment factor of 0.92 or 0.98 used was based on whether the 24-hour urine volume was collected on the last day of the short or long interdialytic period, respectively.…”
Section: Methods Study Cohort: Development and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used the deidentified urine collection database spanning 14 years that was used in a former study (consent not required due to retrospective deidentified data) approved by the University of California, Davis Institutional Review Board (protocol number 806282-1) and an administrative review of the dialysis provider (Dialysis Clinic, Inc) on evaluation of K RU in incident HD patients and theoretical twice-weekly HD. 7 For this study, K RU was determined by multiplying urine volume (Vol) in milliliters with the concentration of urine urea (U urea ) in milligrams per deciliter, divided by an adjusted plasma urea (P urea ) in milligrams per deciliter, which was the pre-HD plasma urea collected on the day that the urine collection terminated. The adjustment factor of 0.92 or 0.98 used was based on whether the 24-hour urine volume was collected on the last day of the short or long interdialytic period, respectively.…”
Section: Methods Study Cohort: Development and Validationmentioning
confidence: 99%
“…Despite the infrequency of RKF measurement in those receiving HD, a large fraction of incident HD patients have substantial residual native kidney function. 7 In addition, the rate of RKF decline in HD may be slow in many cases, with patients garnering the clinical benefits of RKF for longer than what was historically expected. 8 The ideal method of quantifying RKF requires a timed urine collection followed by blood tests with appropriate computations to take into account the duration of collected urine and timing of the last HD treatment.…”
mentioning
confidence: 99%
“…There is disagreement about the definition of incremental dialysis regarding the number of sessions there should be per week and what their scheduling and sequence should be (starting with shorter sessions, increasing frequency first and duration later or starting with fewer sessions of longer duration). Consequently, nutritional indications must once more be contextualized and adapted [21][22][23][99][100][101][102].…”
Section: Concept and Context: A Special Case Incremental Hemodialysismentioning
confidence: 99%
“…This represents a large workload for the nephrologists and the dialysis staff. Chin et al [60] while checking urea clearance in a retrospective cohort of 410 patients, identified 53% suitable for twiceweekly HD. In another recent review, Fernandez-Lucas and Teruel [61] have shown that 76% of incident patients in their dialysis unit during 2014-2015 started HD therapy with twice-weekly sessions.…”
Section: Which Patients Are Suited For Incremental Hd Program and Formentioning
confidence: 99%